Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24129796
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis Identifies Subclusters with Inflammatory Fibroblast Responses in Localized Scleroderma

Abstract: Localized scleroderma (LS) is an autoimmune disease with both inflammatory and fibrotic components causing an abnormal deposition of collagen in the skin and underlying tissue, often leading to disfigurement and disability. Much of its pathophysiology is extrapolated from systemic sclerosis (SSc) since the histopathology findings in the skin are nearly identical. However, LS is critically understudied. Single-cell RNA sequencing (scRNA seq) technology provides a novel way to obtain detailed information at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The reduced expression of PAI-1 , EDN1 , and NFKBIA was confirmed by IHC, while changes in skin tissue expression of MYC were not significant (eFigure 9 in Supplement 1). We also found several sclerosis-mediating genes among the downregulated hub genes, such as CTGF (eFigure 9A in Supplement 1), CXCR4 (eFigure 9F in Supplement 1), IGFBP3 , and THBS1 . To further understand how the cellular immunology of morphea is modulated by sequential fat grafting, we performed an immune cell infiltrate analysis and cell types enrichment analysis.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The reduced expression of PAI-1 , EDN1 , and NFKBIA was confirmed by IHC, while changes in skin tissue expression of MYC were not significant (eFigure 9 in Supplement 1). We also found several sclerosis-mediating genes among the downregulated hub genes, such as CTGF (eFigure 9A in Supplement 1), CXCR4 (eFigure 9F in Supplement 1), IGFBP3 , and THBS1 . To further understand how the cellular immunology of morphea is modulated by sequential fat grafting, we performed an immune cell infiltrate analysis and cell types enrichment analysis.…”
Section: Resultsmentioning
confidence: 90%
“…We also found several sclerosis-mediating genes among the downregulated hub genes, such as CTGF (eFigure 9A in Supplement 1), CXCR4 (eFigure 9F in Supplement 1), IGFBP3, and THBS1. [22][23][24][25][26][27][28] To further understand how the cellular immunology of morphea is modulated by sequential fat grafting, we performed an immune cell infiltrate analysis and cell types enrichment analysis. Both results suggested reduced CD4 + memory T cells after treatment (eFigure 10 in Supplement 1).…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…The same study also demonstrated the crosstalk between fibroblasts and infiltrated immune cells (e.g. macrophages and T cells) to perpetuate inflammatory signals in lesions ( 47 ). Indeed, inflammatory fibrosis was shown to be dependent on CXCL9 and its receptor CXCR3 in a mouse model of skin fibrosis, thereby confirming the involvement of a type-1 immune response in the early phase of skin fibrosis ( 48 ).…”
Section: Localized Sclerodermamentioning
confidence: 77%
“… 25 Another study examining potential disease-associated fibroblasts and related genetic signatures in SSc skin revealed a prevalent myofibroblast-like cluster (SFRP4/PRSS23) that shared numerous upregulated genes expressed in SSc-associated myofibroblasts. 26 Gaydosik et al identified a distinct cluster of recirculating CXCL13 + T cells in SSc skin, expressing a T helper follicular-like gene expression signature, that poised to promote B-cell responses within inflamed tissue. 27 Here, this study sheds light on the potential involvement of APLNR, INS-IGF2 , and RGCC in the pathogenesis of SSc skin through the process of EndMT ( Figure Supplementary 3 ).…”
Section: Discussionmentioning
confidence: 99%